2019
DOI: 10.1084/jem.20181739
|View full text |Cite
|
Sign up to set email alerts
|

Modulating inflammation for cancer therapy

Abstract: This review provides a concise overview of pro- and anti-inflammatory approaches in current tumor therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(88 citation statements)
references
References 129 publications
1
87
0
Order By: Relevance
“…Bars were showed as box and whisker graphs; *p < 0.05, **p < 0.01, ***p < 0.001, and ****p < 0.0001 by two-way ANOVA with Tukey's multiple comparison test. system to act effectively against metastatic tumors [67][68][69] . On this basis, the beneficial effects by checkpoint inhibitors depend on the presence of a pro-inflammatory "hot" environment 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Bars were showed as box and whisker graphs; *p < 0.05, **p < 0.01, ***p < 0.001, and ****p < 0.0001 by two-way ANOVA with Tukey's multiple comparison test. system to act effectively against metastatic tumors [67][68][69] . On this basis, the beneficial effects by checkpoint inhibitors depend on the presence of a pro-inflammatory "hot" environment 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-associated immune cells and their crosstalk with cancer and the components of its microenvironment dramatically affect tumor behavior and patient outcome [1,2]. The concept of cancer immunoediting, represents the dynamic of this interaction, which runs through the phases of elimination, equilibrium and escape, and explains how immunosuppression can overwhelm immunosurveillance [3], eliciting the development of immunological-based approaches to cancer treatment [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Histopathological analysis of experimental and clinical tumors has revealed that, although there is great variability, according to the tumor type and clinical-pathological profile of each patient [5,6], virtually all types of immune cells, including different subsets of T and B lymphocytes, NK and innate lymphoid cells can be part of the tumor microenvironment (TME). However, myeloid cells are the most widely represented, since they might account for up to 50% of the neoplastic mass [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, provision of antioxidants actually increases cancer risk (Jenkins et al, ), and the exact role of oxidative stress (now called redox code; Jones & Sies, ; and never fully elucidated in humans) in cancer aetiology is, to date, still elusive. Conceivably, modulation of the redox code by (poly)phenols (including OOPC) might play some roles in cancer and progression of cancer stem cells, as well as adjunct therapy (Ritter & Greten, ). Such actions are probably not mediated by direct antioxidant activities.…”
Section: Pharmacological and Nutraceutical Properties Of Htmentioning
confidence: 99%